PERSEPSI MASYARAKAT TERHADAP PROGRAM REVEGETASI EKS LAHAN TAMBANG PT TIMAH (Persero) Tbk DI WILAYAH DESA RIDING PANJANG KECAMATAN MERAWANG-KABUPATEN BANGKA1 (PUBLIC PERCEPTION OF USED LAND MINES REVEGETATION PROGRAMâS PT TIMAH (Persero) Tbk IN RIDING PANJ - Tono, E.P.S.B. Taman; Ibrahim, Eddy; Yustian, Indra (PROMINE, 2014)
Reclamation of former mining areas is the end of mining activities (mine closure), aims torestore the function of the land according to the function and designation. The failure of former mining land revegetation program PT Timah (Persero), Tbk was influenced also by the behavior of the people around the former mining areas. Based on the theory of the environment, and human behavior that can affect the continuity of lives and welfare of the environment, so that the necessary research regarding public perceptions of the revegetation program.This study was conducted to analyze the public perception of the success of revegetation programs and the relationship revegetation program on the role of the community around the area of the former mining areas. Research conducted including descriptive qualitative research method and quote purpose sample through questionnaires, direct observations and interviews. The number of respondents was 88 people, that is: 10% of the number of families in the village of Long Riding totaling 878 households. Processing Stage data through a validation test, reliability test, then performed a correlation analysis using Spearman Rank correlation coefficient.The results showed a very strong correlation (0.771 **), the direction and the significance level of 0.01 to the statement PT Timah (Persero) Tbk has been invited and continue to exclude public participation in the implementation of all the ex-mining land reclamation with respondents not amounted to 51.14% agreed with the statement PT Timah (Persero) Tbk, always doing training, coaching and guidance for achieving succession hoarding activities, leveling and replanting former mining land to executors of the community around the former mining areas by the number of respondents 60.23 % disagree.It can be concluded that the tendency of the public perception of PT Timah (Persero), Tbk to include community participation in the implementation of all revegetation programs and training activities, coaching and direction to the achievement by implementing revegetation succession of communities around the former mining areas are still considered less and can not meet the expectations. Suggestions of this study should be of PT Timah (Persero), Tbk to improve and enhance community development methods in revegetation programs and training activities, coaching and direction to the community around the former mining areas.Key words: reclamation, revegetation, perception, participation, used land mine